Dinamika Produksi Dalam Makroekonomi Islam: Analisis Terhadap Prinsip-Prinsip Ekonomi dan Implikasinya Pada Pembangunan Berkelanjutan - Wulan Dayu; Windu Anggara; Isnaini Harahap (Universitas Islam Negeri Sumatera Utara, 2023)
Islamic economic thinking offers unique concepts that influence the way production is carried out, contributes to a fair economy, and is environmentally conscious. In the context of sustainable development, a deeper understanding of how Islamic economic principles can be applied to production processes and their impact on sustainable economic development in Indonesia is essential. The study uses a qualitative analytical approach by analyzing literature related to Islamic economic thinking and production concepts in Islamic macroeconomics. In addition, the research also involves studying production policies and practices based on Islamic economic principles as well as evaluating their impact on economic development and sustainability in Indonesia. The results of the analysis show that Islamic economic thinking emphasizes ethical principles in production, such as justice, social responsibility, and environmental sustainability. These concepts inspire a justice-based production approach and give attention to social and environmental aspects. These principles provide the basis for creating a fair production system, reducing social disparities, and promoting sustainable economic growth. The implications of this study are the importance of considering Islamic economic principles in managing production on a macroeconomic scale.